2013
DOI: 10.4314/ijbcs.v7i1.
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of the leaf extracts of <i>Moringa oleifera</i> and <i>Jatropha curcas</I> on pathogenic bacteria

Abstract: This study evaluates the antimicrobial activity of the leaf extracts of Moringa oleifera and Jatropha curcas against Staphylococcus aureus and Escherichia coli. Different concentrations of the extracts were subjected to these organisms in which Moringa oleifera showed a higher zone of inhibition on Staphylococcus aureus (2.8 cm) while on E. coli (2.4 cm) while Jatropha curcas showed a higher zone of inhibition on E. coli (2.6 cm) while on S. aureus (1.80 cm). The minimum inhibitory concentration (MIC) of Morin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The screening revealed that S. aureus , S. pyogenes , P. aeruginosa , E. coli , and N. gonorrhoeae were all resistant to the extracts. Ojiako (2014) [ 28 ] and Okorondu et al (2013) [ 29 ] previously found that M. oleifera leaf extracts were potent against E. coli and S. aureus when extracted with both the non-polar solvent hexane and the polar solvent ethanol. However, no action against the organisms was found in the current investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The screening revealed that S. aureus , S. pyogenes , P. aeruginosa , E. coli , and N. gonorrhoeae were all resistant to the extracts. Ojiako (2014) [ 28 ] and Okorondu et al (2013) [ 29 ] previously found that M. oleifera leaf extracts were potent against E. coli and S. aureus when extracted with both the non-polar solvent hexane and the polar solvent ethanol. However, no action against the organisms was found in the current investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoid play a role as antibiotic, also tannin and saponin is a fenolic compound which has antibacterial activity. Flavonoids have been reported have antimicrobial activity under laboratory condition through destruction of microbial membrane [22]. So, the bioactive compounds found at M. oleifera seeds promote its potency as antibacterial agent.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing occurrence of antibiotic-resistant strains of bacteria and the spread of multidrug-resistance with reduced sensitivity to antimicrobial agents has compelled intensive searches for effective methods to overcome the therapeutic problem, as well as to discover new infectionfighting approaches [1]. One of the strategies to reduce the resistance to antimicrobial agents is to use antibiotic resistance inhibitors such as that found in traditional medicine [2]. Many plant-based agents used in traditional medicine are considered to be potential or actual therapeutic substitutes to antibiotics, and are considered natural, harmless and inexpensive, yet still effective [3].…”
Section: Introductionmentioning
confidence: 99%